Application of Linear Integer Programming to Optimal Resources Allocation: A Case Study of Mampong Municipal Assembly, Mampong-Ashanti - , Nelson Opoku-Mensah, W. Obeng-Denteh, Isaac Owusu-Mensah, Frimpong Wiafe (Archives of Current Research International, 2016)
The problem of allocating resources at the Mampong Municipal Assembly, Mampong-Ashanti with the aim of minimizing unnecessary lapses during budget allocation for resources by the assembly was considered. The problem was formulated as an Integer Linear Programming (ILP) problem using the available data from the Municipal Assembly. It was found that out of the twelve different locations considered and budget of Eight Hundred and Seventy Thousand Ghana Cedis, the optimal number of classroom to be built was thirty three (33) representing a three 3-unit classroom and four 6-unit classroom buildings at seven different locations within the Municipal at a minimum budget of Eight Hundred and Seven Thousand Ghana Cedis (GH¢ 807,000) respectively. We concluded that the Knapsack problem for selecting required sites in critical situations such as construction of school buildings was useful and it can be applied to any situation where allocation of funds in the sector of educational development becomes a serious setback. All of this will be achieved by using software called quantitative management which helps in solving and analyzing such problems.